2017
DOI: 10.1039/c6ra28229f
|View full text |Cite
|
Sign up to set email alerts
|

Targeting selenium nanoparticles combined with baicalin to treat HBV-infected liver cancer

Abstract: Herein, we demonstrate baicalin-loaded selenium nanoparticles with a liver-targeting folic acid moiety to treat HBV-infected liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…Baicalin (7-D-glucuronic acid-5,6-dihydroxyflavone, purity > 95%) was purchased from Aladdin Company, Shanghai, China, and dissolved in polyethylene glycol (PEG, provided by Department of Chemistry, Jinan University, Guangzhou, China). As a kind of nontoxic solvent, PEG increased the solubility of baicalin [ 12 ], which also improved the bioavailability. Ribavirin (H51023508) was produced by Sichuan Baili Pharmaceutical Company, Sichuan, China.…”
Section: Methodsmentioning
confidence: 99%
“…Baicalin (7-D-glucuronic acid-5,6-dihydroxyflavone, purity > 95%) was purchased from Aladdin Company, Shanghai, China, and dissolved in polyethylene glycol (PEG, provided by Department of Chemistry, Jinan University, Guangzhou, China). As a kind of nontoxic solvent, PEG increased the solubility of baicalin [ 12 ], which also improved the bioavailability. Ribavirin (H51023508) was produced by Sichuan Baili Pharmaceutical Company, Sichuan, China.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, DDS conjugated with targeting ligands have been widely adopted in previous articles to increasing the tumor-homing capability while at the same time reducing the unwanted side effects of the modified DDS. [12,13] In the last decade, monoclonal antibodies capable of targeting corresponding receptors on cancer cell surface and exert corresponding functions are considered as promising chemotherapy candidates for effective cancer therapy. [14,15] Trastuzumab (Tra) is a commonly adopted monoclonal antibody that has high affinity to human epidermal growth factor receptor 2 (HER2) and inhibits its following signaling within cancer cells via specific binding.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were cultured as described previously. 26 Cytotoxicity assay was also performed as previously reported. 26 The fluorescence images stained with calcein AM (green) and PI (red) and thermal images of MCF-7 cells with different treatments were taken by fluorescence microscopy (ZEISS Observer, Z1) and thermal imager, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…23 Selenium nanoparticles (SeNPs) have been studied and proposed as excellent nanomedicines for anti-tumor drugs and drug carrier because of their high anti-tumor activity, superior anti-oxidation, low toxicity to normal cells, and good biocompatibility and degradability. Chen's group [24][25][26][27] reported that SeNPs induced apoptosis in tumor cells by causing intracellular oxidative stress, mitochondrial dysfunction and simultaneous inhibition of cancer growth, migration and invasion. Kim's group 28 reported that silicacapped gold nanorods covered with Se coating (Se@Au@mSiO 2 /DOX) suppressed tumor cell growth by cell cycle arrest and induced apoptosis via suppression of the Src/FKA/AKT signaling pathways.…”
Section: Introductionmentioning
confidence: 99%